2016
DOI: 10.1111/aor.12807
|View full text |Cite
|
Sign up to set email alerts
|

A Dermal Equivalent Engineered with TGF‐β3 Expressing Bone Marrow Stromal Cells and Amniotic Membrane: Cosmetic Healing of Full‐Thickness Skin Wounds in Rats

Abstract: Transforming growth factor beta-3 (TGF-β3) has been shown to decrease scar formation after scheduled topical applications to the cutaneous wounds. This study aimed to continuously deliver TGF-β3, during the early phase of wound healing, by engineering a dermal equivalent (DE) using TGF-β3 expressing bone marrow stromal cells (BM-SCs) and human dehydrated amniotic membrane (hDAM). To engineer a DE, rat BM-SCs were seeded on the hDAM and TGF-β3 was transiently transfected into the BM-SCs using a plasmid vector. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…TGF-b3 significantly decreased scar size in both phase I and II clinical trials, though complete regeneration was never achieved and it failed to meet efficacy standards in phase III. 7,8 In the case of therapeutics for both chronic wounds and scar prevention, it is believed that improved delivery methods that permit sustained release may facilitate clinical effectiveness.…”
Section: Clinical Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…TGF-b3 significantly decreased scar size in both phase I and II clinical trials, though complete regeneration was never achieved and it failed to meet efficacy standards in phase III. 7,8 In the case of therapeutics for both chronic wounds and scar prevention, it is believed that improved delivery methods that permit sustained release may facilitate clinical effectiveness.…”
Section: Clinical Relevancementioning
confidence: 99%
“…However, since temporal variation critically affects healing, continuing studies are exploring the efficacy of continuously delivering TGF-b3 in de- creasing scarring. 7 M6P is a potent inhibitor of TGF-b1 and TGF-b2. While it was successful in phase I clinical trials, in the phase II exploratory trial neither topical nor intradermal application showed statistical significance.…”
Section: Therapeutic Strategies Targeting the Immune System For Skin mentioning
confidence: 99%
“…AAMs preserve the tissue ECM properly and have a potential use as a membrane for skin wound healing. TGF- β 3 expressing bone marrow stromal cells cultured on AAM as a dermal equivalent led to the deposition of parallel, uniform collagen bundles with improved cosmetic appearance and decreased scar formation when transplanted onto full-thickness excisional skin wounds in rats for 85 days [129]. The decellularized matrix can serve as ready-to-use tissue models with essential ECM molecules like collagen, elastins, GAGs, and growth factors for improved cell attachment and proliferation.…”
Section: Biomaterials For Scaffold Fabricationmentioning
confidence: 99%
“…Finally, using previously described parental cell-based and direct methods, therapeutic molecules including drugs, mRNAs, miRNAs, siRNAs, peptides, growth factors, anti-scarring factors (transforming growth factor [TGF]β1 inhibitors such as decorin and TGFβ3 [ 121 , 122 ]), and wound healing factors (SDF-1, which has a chemotactic function for bone marrow MSCs [BMSCs] and endothelial progenitor cells [EPCs] in vascularization and healing [ 123 ]) can be efficiently loaded (as fully described in Sect. 3.1) into the regenerative engineered exosomes.…”
Section: Clinical Applications Of Designer Exosomesmentioning
confidence: 99%